Answer:
![A(1)=9](https://tex.z-dn.net/?f=A%281%29%3D9)
![A(2)=4](https://tex.z-dn.net/?f=A%282%29%3D4)
![A(3)=-1](https://tex.z-dn.net/?f=A%283%29%3D-1)
Arithmetic sequence
Step-by-step explanation:
We are given that
A(1)=9
We have to find first three terms and identify the sequence is geometric or arithmetic.
Substitute n=1
Then, we get
![A(2)=A(1)-5=9-5=4](https://tex.z-dn.net/?f=A%282%29%3DA%281%29-5%3D9-5%3D4)
For n=2
![A(3)=A(2)-5=4-5=-1](https://tex.z-dn.net/?f=A%283%29%3DA%282%29-5%3D4-5%3D-1)
For n=3
![A(4)=-1-5=-6](https://tex.z-dn.net/?f=A%284%29%3D-1-5%3D-6)
![d_1=A_2-A_1=4-9=-5](https://tex.z-dn.net/?f=d_1%3DA_2-A_1%3D4-9%3D-5)
![d_2=A_3-A_2=-1-4=-5](https://tex.z-dn.net/?f=d_2%3DA_3-A_2%3D-1-4%3D-5)
![d_3=A_4-A_3=-6+1=-5](https://tex.z-dn.net/?f=d_3%3DA_4-A_3%3D-6%2B1%3D-5)
![d_1=d_2=d_3=-5](https://tex.z-dn.net/?f=d_1%3Dd_2%3Dd_3%3D-5)
When the difference of consecutive terms are constant then the sequence is arithmetic sequence.
Therefore, given sequence is arithmetic sequence.
<u>Part 1)</u> "Four times the difference of a number and
is
"
Let
x--------> the number
we know that
the expressions is equal to
![4(x-7)=32](https://tex.z-dn.net/?f=%204%28x-7%29%3D32%20)
therefore
<u>the answer part 1) is</u>
![4(x-7)=32](https://tex.z-dn.net/?f=%204%28x-7%29%3D32%20)
<u>Part 2)</u> "One third of a number is
less than the number itself"
Let
x--------> the number
we know that
the expressions is equal to
![\frac{1}{3} x=(x-12 )](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B3%7D%20x%3D%28x-12%20%29%20%20)
therefore
<u>the answer part 2) is</u>
![\frac{1}{3} x=(x-12 )](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B3%7D%20x%3D%28x-12%20%29%20%20)
<u>Part 3)</u> "Ten increased by the quotient of a number and
is
"
Let
x---------> the number
we know that
the expressions is equal to
![10+ (\frac{x}{2} )= -15](https://tex.z-dn.net/?f=%2010%2B%20%28%5Cfrac%7Bx%7D%7B2%7D%20%29%3D%20-15%20%20%20)
therefore
<u>the answer Part 3) is</u>
![10+ (\frac{x}{2} )= -15](https://tex.z-dn.net/?f=%2010%2B%20%28%5Cfrac%7Bx%7D%7B2%7D%20%29%3D%20-15%20%20%20)
<u>Part 4)</u> "One less than the product of a number and
is
more than the number itself"
Let
x---------> the number
we know that
the expressions is equal to
![(3x)-1=5+x](https://tex.z-dn.net/?f=%20%283x%29-1%3D5%2Bx%20)
therefore
<u>the answer Part 4) is</u>
![(3x)-1=5+x](https://tex.z-dn.net/?f=%20%283x%29-1%3D5%2Bx%20)
Answer:B
Step-by-step explanation:
<u><em>Answer:</em></u>
y^2 = 28x
<em><u>Step-by-step explanation:</u></em>
Since the directrix is horizontal, use the equation of a parabola that opens left or right.
(y−k)^2 = 4p(x−h)
Find the vertex.
(0,0)
Find the distance from the focus to the vertex.
p = 7
Substitute in the known values for the variables into the equation
(y−k)^2 = 4p(x−h).
(y−0)^2 = 4(7)(x−0)
Simplify.
<em>y^2 = 28x</em>